151k views
2 votes
Does anyone know the actual answer to this and could help me that would be nice

Does anyone know the actual answer to this and could help me that would be nice-example-1
User Ravi Singh
by
6.7k points

1 Answer

4 votes

Answer:

see explanation

Explanation:

Given

-
(1)/(2) [ -
(3)/(2) c + 6c + 1 ] - 3c

Distribute the square bracket by -
(1)/(2)

=
(3)/(4\\) c - 3c -
(1)/(2) - 3c

Collect like terms

=
(3)/(4) c - 6c -
(1)/(2)

=
(3)/(4) c -
(24)/(4) c -
(1)/(2)

= -
(21)/(4) c -
(1)/(2)

User Yonasstephen
by
5.7k points